Financial management - Pinder-Ayres, Brian (Creative business essentials., 2016)
Most newly qualified architects have scant knowledge about the practicalities of running a practice and in particular the challenges of managing the financial side of the business. This book highlights the major financial risks and how these can be avoided. The chapters give straightforward advice and practical solutions based on the author's years of hard-won experience. Friendly, clear and concise, it will give you all the knowledge and tools you need to plan for business success. Based on the original Good Practice Guide, this updated and re-designed version is now even more comprehensive and contains detailed information on fees, as well as real life anecdotal advice from practitioners, updated references, and is in line with the latest legislation. This is invaluable reading for sole and small practitioners of architecture and other creative industries.